ANALYZING THE CONSUMER PURCHASING INTENTION OF VIRTUAL GOODS IN ONLINE GAME - Warouw, Elfan Frederick Hizkia (FEB Universitas Sam Ratulangi Manado, 2014)
Online game is a virtual world environment that many people called as gamer joins to find pleasure of gaming. In purpose to reach the gamers goal, they need to improve the competency of their character by using virtual goods. Three consumer value such as functional value with price utility and quality as it variables, emotional value with aesthetics and playfulness as it variables, and social value with social self-image and social relationship had involved in this research in order to get the result. This study objective is to find out what factor that affected the intention of the gamer to purchase the virtual goods. Gamers in Manado city are the purpose of this study. This research is a quantitative research that associative with multiple linear regression analysis technique. The population of the sample is the active only gamer in Manado city that the numbers of the online gamers are unidentified. This research used accidental sampling as the method with 100 respondents. The result of the research then shows that three from six variables which are Aesthetics, Playfulness, and Price Utility has significant effect to Purchasing Intention. Keywords: functional value, emotional value, social value, purchasing intention, virtual goods.